The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.4995/wrs.2018.7362
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and phylogenetic analysis of laboratory rabbits in Taiwan based on microsatellite markers

Abstract: Laboratory rabbits used in Taiwan are primarily supplied by the Livestock Research Institute (LRI) and the Animal Drugs Inspection Branch (ADIB) of the Animal Health Research Institute. An analysis of the genetic characteristics and structure of these populations would thus be a fundamental step in building a long-term management programme for maintaining stable animal quality and preserving the genetic variation among the populations. In this study, DNA samples were isolated from founders of 5 populations: Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Moreover, results in Table S2 showed that 57 % of loci were highly formative in terms of PIC values. The high percentage of formative PIC was also observed in several studies (Alves et al, 2015;El-Aksher et al, 2016;Lai et al, 2018). On the other hand, 89 % of the loci were significant in terms of HWE at three significance levels (P <0.05, P <0.01, and P <0.001), which is generally characteristic for an inbreeding situation in NARs.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, results in Table S2 showed that 57 % of loci were highly formative in terms of PIC values. The high percentage of formative PIC was also observed in several studies (Alves et al, 2015;El-Aksher et al, 2016;Lai et al, 2018). On the other hand, 89 % of the loci were significant in terms of HWE at three significance levels (P <0.05, P <0.01, and P <0.001), which is generally characteristic for an inbreeding situation in NARs.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, the genetic information provided by morphological and biochemical markers is limited; hence, they are not used to identify single base mutations. Owing to the difficultly in comprehensively evaluation the genetic background of laboratory animal, molecular marker technology have been introduced into the study of genetics, such as SSRs, which can provide sufficient genetic information, and have become available for detection of genetic diversity of laboratory animals [5]. However, as a third-generation DNA molecular marker technology and an excellent tool for population based genetic research [6,7], the research of using single nucleotide polymorphisms (SNPs) in genetic variability evaluation of closed colony is still inadequate.…”
Section: Introductionmentioning
confidence: 99%